Evaluation of 25% Poloxamer As a Slow Release Carrier for Morphine in a Rat Model - Sulimai, Nurul H.; Ko, Jeff C.; Jones-Hall, Yava L.; Weng, Hsin-Yi; Deng, Meng; Breur, Gert J.; Knipp, Gregory T. (Frontiers in Veterinary Science, 2018)
The objectives of this study were to evaluate poloxamer as a slow release carrier for morphine (M) and potential tissue irritation after subcutaneous poloxamer–morphine (PM) injection in a rat model. Based on the result of a previous in vitro work, 25% poloxamer, with and without morphine, and saline were administered in 14 rats’ flanks. Blood for morphine concentrations was automatically sampled at multiple preprogrammed time points using the Culex™ unit for 48 h. Skin tissues from the injection sites were harvested and evaluated for histopathological changes. Following M or PM administration, it was determined that the half-life (t1/2) was significantly longer in the PM (5.5 ± 7.2 h) than M (0.7 ± 0.8 h) indicated a slow dissolution of poloxamer with morphine. The tmax was within 15 min and Cmax was approximately three times higher with M than with PM, reaching 716.8 (±153.7 ng/ml) of plasma morphine concentrations. There was no significant difference in total area under the curve and clearance of M versus PM. Histology inflammatory scores were similar between M, PM, and poloxamer but were significantly higher than saline control. We concluded that 25% poloxamer was capable of increasing the t1/2 of morphine, without a significant tissue irritation.